Azerbaijan : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
The Country Procurement Assessment Report (CPAR) reviews Azerbaijan's public sector procurement structure, including the new legal framework, organizational responsibilities and capabilities, and present procedures and practices. It also looks at how these practices may differ from the formal rules and procedures. In each area, including the legal and regulatory framework, fraud and corruption, the State Procurement agency, control and review, procurement procedures, public sector management performance, bank-assisted projects, private sector competitiveness, private sector performance, and the general business environment, the CPAR makes specific recommendations for action. The report makes a general assessment of the institutional, organizational and other risks associated with the procurement process; establishes the basis for dialogue between the country and donors on how to streamline and improve the economy, efficiency and transparency of public sector procurement; develops a detailed action plan for reform to achieve institutional improvements, including interim modifications to existing practices; and encourages better commercial practices in the private sector.